PERMINTAAN DAN KEPUASAN KONSUMEN RUMAH TANGGA DALAM MENGONSUMSI SUSU BUBUK DI BANDAR LAMPUNG - Ervina Virgawati Putri; Fembriarti Erry Prasmatiwi; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
The purposes of this research are to investigate the demand of powdered milk at the household level, to know what factors that influence the demand, to analyze satisfaction level and to know the influencing factors of household consumer satisfaction on consuming powdered milk in Bandar Lampung.  This research was conducted by purposive survey method in traditional, modern, and minimarket in Bandar Lampung.  The samples of this research were 80 people that taken by accidental sampling method.  Data collection was conducted from August until November 2014.  The demand level and its influencing factors were analyzed by using Cobb Douglass function, satisfaction of consuming powdered milk was measured by costumer satisfaction index (CSI), where as the factors that influenced household consumer satisfaction was analyzed by logistic regression analysis.  The result of this research showed that demand of powdered milk which consumed by household consumer was 670 g/ month.  The factor that influenced powdered milk demand was powdered milk cost, liquid milk cost, and income level.  There were 61 consumers felt satisfy with powdered milk performance.  Factors that influence consumer satisfaction level was powdered milk cost and buying location. Key words: consuming, demand, powdered milk, satisfaction